Work-Life Balance Before and During Work from Home in a Covid-19 Pandemic Situation - Veronika Agustini Srimulyani; Y. Budi Hermanto (Jurnal Manajemen Indonesia, 2022)
Corona Virus Disease (Covid-19) is a global pandemic that affects the work systems of employees and influences the work-life balance employees. This empirical study was conducted on teachers and lecturers in Indonesia who had to implement a remote work system or work from home to prevent the spread of Covid-19. The objectives of this study were: 1) to analyze the advantages and disadvantages of working from home; 2) to analyze the differences in work-life balance between teachers and lecturers in Indonesia,before and during the Covid-19 pandemic. The questionnaire distribution survey was done through the Google form application, which was distributed through social media such as Facebook, Messenger, WhatsApp Group, and e-mail to the teacher and lecturer communities. Respondents willing to participate in filling out the questionnaire were 108 participants, consisting of 52 lecturers and 56 teachers from various educational organizations in several Indonesian provinces. The analysis showed that there were several advantages and disadvantages to working from home. Advantages that were generally felt by educators included flexible working time, closeness to family, increased technological mastery, and maintained health. Disadvantages that were generally felt wereirregular rhythms/patterns of work, which cause unclear work and non-work boundaries, and an increase in operational costs such as the internet and electricity. The results of the statistical analysis of the Paired Sample t-Test revealed that: 1) there was a significant difference in the work-life balance of educators before and during work from home; 2) from the teacher group, there was an increase in the aspect of work-life balance during work from home. However, statistically, the difference was not significant. While from the lecturer group, statistically, the increase in work-life balance was significant.Keywords-Covid-19, Work from home, Work-life balance.